Advertisement Remove all ads

Evaluate: (M + 3) (M − 3) (M2 + 9) - Mathematics

Sum

Evaluate: (m + 3) (m − 3) (m2 + 9)

Advertisement Remove all ads

Solution

(m + 3) (m − 3) (m2 + 9)

= (m)2 − (3)2 (m2 + 9) ......[ ∵ (a − b) (a + b) = a2 − b2]

= (m2 − 9) (m2 + 9)

= (m2)2 − 92

= m4 − 81

Concept: Product of Sum and Difference of Two Terms
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Mathematics Class 8 ICSE
Chapter 12 Identities
Exercise 12 (D) | Q 2.07 | Page 155
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×